Clinical and neurocognitive aspects of hallucinations in Alzheimer's disease. (December 2017) - El Haj, Mohamad; Roche, Jean; Jardri, Renaud; Kapogiannis, Dimitrios; Gallouj, Karim; Antoine, Pascal
Highlights: Hallucinations are the most frequent psychotic symptom in Alzheimer's disease (AD) Hallucinations in AD are associated with neurological and genetic factors They are also associated with cognitive, affective, and iatrogenic factors Abstract: Due to their prevalence, hallucinations are considered as one of the most frequent psychotic symptoms in Alzheimer's disease (AD). These psychotic manifestations reduce patients' well-being, increase the burden of caregivers, contribute to early institutionalization, and are related with the course of cognitive decline in AD. Considering their consequences, we provide a comprehensive account of the current state of knowledge about the prevalence and characteristics of hallucinations in AD. We propose a comprehensive and testable theoretical model about hallucinations in AD: the ALZHA (ALZheimer and HAllucinations) model. In this model, neurological, genetic, cognitive, affective, and iatrogenic factors associated with hallucinations in AD are highlighted. According to the ALZHA model, hallucinations in AD first involve trait markers (i.e., cognitive deficits, neurological deficits, genetic predisposition and/or sensory deficits) to which state markers that may trigger these experiences are added (e.g., psychological distress and/or iatrogenic factors). Finally, we provide recommendations for assessment and management of these psychotic manifestations in AD, with the aim to benefit patients, caregivers, and health professionals.